An NP's guide to current physical activity recommendations. Issue 9 (September 2020) - Hudson, Geoffrey M.; Hauff, Caitlyn; Hayes, Katey; Fruh, Sharon
Abstract : Abstract: Physical inactivity is a public health crisis that contributes to many of the chronic diseases that affect Americans. This review emphasizes the beneficial health implications of physical activity along with the dangers of sedentary lifestyles. It also provides advice tailored to NPs to help their patients become more physically active. Abstract : Physical inactivity is a public health crisis that contributes to many of the chronic diseases that affect Americans. This review emphasizes the beneficial health implications of physical activity along with the dangers of sedentary lifestyles. It also provides advice tailored to NPs to help their patients become more physically active.